Social media deception - Steffens, Bradley, 1955- (Risks of social media., 2021)
"Social media brings friends and family closer together, but it brings criminals and victims closer together, too. False memes, ads, posts, and pictures are damaging the reputations of individuals, businesses, and even political leaders. Fake accounts are launching scams that lead to hacks and even ransom demands. [This book] . . . presents a realistic picture of what is happening on social media, who's most affected, and what is being done to address these troubling issues."--Provided by publisher.